(untitled) (Research, Society and Development, 2021)
Oenocarpus distichus Mart. is a native Amazonian palm tree with great socioeconomic potential for the pulp. However, fruit production is still dependent on extractivism and the information available on the nutritional composition of the pulp is still scarce, constituting limiting factors to its knowledge. In this work, 41 samples of pulp from three locations in Pará were analyzed for pH, total titratable acidity, total soluble solids, moisture, ash, fiber, protein and lipids. The data were analyzed using univariate and multivariate analysis. The pulps showed significant differences among them for the nine characteristics, forming by the mean comparison test eight (TSS) to sixteen (lipids, carbohydrates and others) distinct groups. By cluster analysis, the pulps were separated into seven different groups. Group 1 had the highest fiber (18.14%) and carbohydrate (46.98%) contents, Group 2 had the highest values for TCA (1.05%), TSS (2.53 °Brix) and ash (3.11%), and Group 4 had the highest content of lipids (71.99%). The significant variation among the pulps of this species from the same locality can be attributed to environmental (fruit ripening stage, post-harvest handling, etc.) and genetic factors. O. distichus pulps from different locations in the state of Pará, Brazil, have different composition, forming several distinct groups. The divergence in these pulps is higher within than among localities. In general, bacaba pulp has high nutritional value for being rich in lipids, carbohydrates and proteins, being an excellent source of fiber.